The courage to be - Tillich, Paul, 1886-1965; Gomes, Peter J. (New Haven : Yale University Press, 2000)
The great Christian existentialist thinker Paul Tillich describes the dilemma of modern man and points a way to the conquest of the problem of anxiety. This edition includes a new introduction by Harvey Cox that situates the book within the theological conversation into which it first appeared and conveys its continued relevance in the current century.
Being and courage -- Being, nonbeing, and anxiety -- Pathological anxiety, vitality, and courage -- Courage and participation (the courage to be as a part) -- Courage and individualization (the courage to be oneself) -- Courage and transcendence (the courage to accept acceptance).
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Courage; Ontology; Anxiety; Existentialism; Anxiety in literature -- Religious aspects; Modernism (Literature) -- Religious aspects; Religion; Anxiety; Existentialism; Religion; Courage; Ontologie; Existentialisme; Modernisme (Littérature) -- Aspect religieux; Religion; ontology (metaphysics); existentialism; religion (discipline); PSYCHOLOGY -- Psychopathology -- Anxieties & Phobias; SELF-HELP -- Anxieties & Phobias; PHILOSOPHY -- Religious; Religion; Anxiety; Courage; Existentialism; Ontology